Evaluation Of Subcooling With Liquid-Suction Heat Exchanger On The Performance Of Air Conditioning System Using R22/R410A/R290/R32 As Refrigerants - Sukri, Mohamad Firdaus; Rachmad, Imbang Tritjahjono; Kasni, Sumeru; Andriyanto, Setyawan (Penerbit Akademia Baru, 2019)
This paper presents a numerical study to investigate the effect of subcooling with liquid-suction heat exchanger (LSHX) on the performance of air conditioning system using R22, R410A, R290 and R32 as refrigerants. In the near future, R290 and R32 refrigerants are projected to replace R22 and R410A as working fluids in the residential air conditioning. In this study, four parameters, i.e., the refrigerating effect, compressor work, COP and discharge temperature were investigated. In the numerical modelling, the evaporating and condensing temperatures were assumed constant at 5 oC and 40oC, respectively. The results showed that the COP improvements increased with the increase in the subcooling. R32 and R290 had the lowest and the highest COP improvement when subcooling was applied, i.e., 3.3% and 5.3% for subcooling of 5K and 6.2% and 10.2% for subcooling of 10K, respectively. Due to low global warming potential and almost identical refrigerant properties as compared to R22, system with LSHX and R290 has huge commercial potential as a replacement for conventional system in the future